2007
DOI: 10.1111/j.1467-789x.2007.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Policy options for responding to the growing challenge from obesity in the United Kingdom

Abstract: The aim of this study was to map and analyse how key stakeholders evaluated options for dealing with the rising incidence of obesity in the UK, as part of a wider cross-national study in nine European countries. Multi-criteria mapping was used to capture the ways in which different policy options were evaluated by a variety of key stakeholders. 'Positive societal benefits' was among the criteria most often selected by participants to assess the options and was generally considered more important than costs. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Respondents also indicated that they were dependent on other policy sectors for achieving their own goals. As in our study, respondents in other research also shared the opinion that a single policy measure will not be sufficient to tackle complex health problems such as obesity and that an integral (and multi-sector) approach is warranted [29]. In conclusion, these findings indicate that there is room for expansion of multi-sector collaboration, and that this could have a potential stimulating effect on integrated health policy action.…”
Section: Further Enhancing Multi-sector Collaborationsupporting
confidence: 58%
“…Respondents also indicated that they were dependent on other policy sectors for achieving their own goals. As in our study, respondents in other research also shared the opinion that a single policy measure will not be sufficient to tackle complex health problems such as obesity and that an integral (and multi-sector) approach is warranted [29]. In conclusion, these findings indicate that there is room for expansion of multi-sector collaboration, and that this could have a potential stimulating effect on integrated health policy action.…”
Section: Further Enhancing Multi-sector Collaborationsupporting
confidence: 58%
“…Respondents used a five‐point scale (strongly oppose to strongly support) to evaluate 15 possible interventions designed to reduce overweight and obesity among the population. We identified these interventions by reviewing recent literature, examining policy documents and consulting with public health experts 9,20–23 . Each measure tested had been suggested by politicians, policy analysts or other researchers and was chosen after reviewing submissions on obesity to a recent government enquiry, in which several authors were involved 3,4 .…”
Section: Methodsmentioning
confidence: 99%
“…Third, regulating school/canteen meals is more likely to help students not to skip breakfasts and improve their healthy eating choices through improvement in terms of availability, but in the case of school meals regulations, they need to be comprehensive and also involve the parents (15,55,56) . Because combinations of policies, such as with NKP (26) and FLVS (31) , have been better evaluated, either because of their long-standing life or their design, the evidence suggests that any policy aimed at healthy eating may be successful if there is a component of multi-stakeholder involvement and if the approach includes the synergy of different types of policy instruments (57) . Furthermore, the present study emphasises the need for harmonised and verifiable indicators for measuring success and comparing between countries, and advocates for better informed (evidence based) policy choices.…”
Section: Discussionmentioning
confidence: 99%